2014
DOI: 10.1007/s13204-014-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies and luminescence properties of CeO2:Eu3+ nanophosphors synthesized by oxalate precursor method

Abstract: A novel synthesis strategy to prepare CeO 2 :Eu 3? nanophosphors and its luminescence behavior is reported. Different structural characterization techniques such as X-ray diffraction, transmission electron microscope and thermogravimetric analysis reveal that thermal decomposition of oxalate precursor is an effective pathway to produce rare earth oxide nanocrystals. Optical characterizations of the CeO 2 :Eu 3? were done by UV-Visible absorption, photoluminescence excitation and emission spectra. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…At low doping concentrations, the Eu 3+ ions mainly enter into the lattice with inversion symmetry. With the increased Eu 3+ doping, they can replace Ce 4+ and create symmetry distortions to cause the electric dipole transitions [6]. In the present case, the 5 D 0 !…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…At low doping concentrations, the Eu 3+ ions mainly enter into the lattice with inversion symmetry. With the increased Eu 3+ doping, they can replace Ce 4+ and create symmetry distortions to cause the electric dipole transitions [6]. In the present case, the 5 D 0 !…”
Section: Resultsmentioning
confidence: 68%
“…The absence of electrons in the 4f shell makes CeO 2 an ideal host material for europium. By doping Eu 3+ ions into CeO 2 host, it can encourage effective energy transfer from the Ce 4+ -O 2host to Eu 3+ ions and greatly enhance the luminescent properties [6]. Moreover, since the ionic radius of Eu 3+ (0.1066 nm) is close to that of Ce 3+ (0.1143 nm) and Ce 4+ (0.097 nm), it favors extensive solubility of Eu 3+ within the ceria lattice [7].…”
Section: Introductionmentioning
confidence: 99%
“…The spectra exhibit a wide and strong excitation band due to the charge transfer from O 2-to Ce 4? in the wavelength region 300-370 nm [18,29]. It is found that the charge transfer band shifts to a lower energy when the annealing temperature increases.…”
Section: Optical Characterizationsmentioning
confidence: 96%
“…One of the simple, effective and low-cost CeO2 synthesis routes is oxalic precipitation followed by a calcination step [7][8][9][10]. The process takes advantage of the high insolubility of oxalate salts to recover REEs.…”
Section: Introductionmentioning
confidence: 99%